G Benefits of Leased Objects Renting Through the Boterindriver Application Perspective of MUI Fatwa No/09/DSN-MUI/IV/2000 - Siregar, Gindo; Zahara, Fatimah (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2023)
In accordance with technological developments, many applications provide transportation services for the community, especially in driver applications. Many people want to become driver partners because the requirements are easy and it's also free when joining as a driver. This makes the online motorcycle taxi's income to be small. The impact of these conditions resulted in unhealthy competition between drivers. One of them is by adding features, namely the boteridriver application. The boteridriver application is an illegal application made by someone to earn more income by manipulating data, location, and distance. The focus of this research is to find out the practice of using the driver application in the city of Medan and the views according to the MUI fatwa No/09/DSN-MUI/IV/2000 regarding the practice of renting driver applications in the city of Medan. This type of research is qualitative research using field methods and by conducting interviews with online motorcycle taxi drivers and the public. The results of this study will conclude that the practice of using the boteridriver application only provides a few advantages for users and receives many disadvantages for users of the boteridriver application, the public, companies and drivers who do not use the application. The Boteridriver application rental prices vary, where the practice of renting the Boteridriver application used by online motorcycle taxi drivers is not in accordance with Islamic sharia provisions placing its placement in MUI fatwa No/09/DSN-MUI/IV/2000 which applies to the public.